Impact of epidermal growth factor on the treatment of diabetic foot ulcers - Wilver Velázquez; Alfredo Valles; Walfrido Curbelo (Biotecnología Aplicada)
Human Epidermal Growth Factor (hEGF), obtained through recombinant DNA technology and formulated as Heberprot-P at a dosage of 75 µg, can stimulate the granulation and cicatrization of different tissues. This work is aimed mainly at the evaluation of the impact of the intralesional administration of hEGF in diabetic foot ulcers (DFU) treated with the optimized insulin scheme, in terms of whether it facilitates granulation and cicatrization or decreases the number of amputations. An evaluative, longitudinal intervention method was applied in 32 patients with a diagnosis of Diabetic Foot that complied with the inclusion criteria (Wagner grade 3 and 4 ulcers, patient older than 18 years, signed informed consent form), excluding cases where ulcer area was smaller than 1 cm2 or there were decompensated chronic diseases: diabetic coma, ischemic cardiopathy, CRI (creatinine > 200 mmol/L, oligoanuria and antecedents or suspicions of malignant disease) and applying the treatment intralesionally, thrice per week. Both granulation and cicatrization of the lesions were achieved in 90.62% of the cases in an average time of 46.5 days ± 8.9. Amputation was necessary only in 9.38% of the cases. The most frequent adverse events were pain, burning sensations, and shivering. The therapeutic scheme of intralesional administration of Heberprot-P can complete lesion closure and is a convenient and safe alternative in the treatment of advanced diabetic foot ulcers, constituting a unique therapeutic modality for a critical and incapacitating disease.